Lab-scale pyrolysis of the Automotive Shredder Residue light fraction and characterization of tar and solid products. (June 2017) - Anzano, Manuela; Collina, Elena; Piccinelli, Elsa; Lasagni, Marina
Highlights: Car fluff was pyrolysed at various temperatures. Condensable gases (tar) and solid residue obtained were characterized. Char had low HHV, high metal content and low PAH concentration. Tar had high HHV and can be used as an alternative fuel. Toxicity of tar changes with temperature, the greatest contribution is from PCDFs. Abstract: The general aim of this study is the recovery of Automotive Shredder Residue (ASR). The ASR light fraction, or car fluff, that was collected at an Italian shredding plant was pyrolysed at various temperatures (500–800 °C) in a lab-scale reactor. The condensable gases (tar) and solid residue yields increased with decreasing temperature, and these products were characterized to suggest a potential use to reclaim them. The higher heating value (HHV) of tar was 34–37 MJ/kg, which is comparable with those of fossil fuels. Furthermore, the ash content was low (0.06–4.98%). Thus, tar can be used as an alternative fuel. With this prospect, the concentrations of polychlorinated dibenzodioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in tar were determined. The toxicity of tar changes with temperature (1–5 ng I-TEQ/g), and the PCDFs significantly contribute to tar toxicity, which was 75–100% with a maximum of 99.6% at 700 °C. Regarding the characterization of the solid residue, the low HHV (2.4–3.3 MJ/kg) does not make it suitable for energy recovery. Regarding material recovery, we considered its use as a filler in construction materials or a secondary source for metals. It shows a high metal concentration (280, 000–395, 000 mg/kg), which is similar at different pyrolysis temperatures. At 500 °C, polycyclic aromatic hydrocarbons (PAHs) were not detected in the solid residue, whereas the maximum total PAH concentration (19.41 ng/g, 700 °C) was lower than that in fly ash from MSWI. In conclusion, 500 °C is a suitable pyrolysis temperature to obtain valuable tar and solid residue.